PENERAPAN REGRESI COMPLEMENTARY LOG-LOG DALAM ANALISIS KEMISKINAN ANAK DI DAERAH PERKOTAAN DI PROVINSI BENGKULU TAHUN 2018 - Maria Megachita da Silva; Agung Priyo Utomo (Seminar Nasional Official Statistics, 2020)
Child poverty is a problem that needs special attention, considering that children are the future generation of the nation. Child poverty is closely related to household poverty. Through a monetary approach, a child aged 0-17 years is said to experience poverty if he lives in a household with average per capita monthly expenditure below the poverty line. The locus of this research is Bengkulu Province, based on finding that the level of child poverty in Bengkulu Province is highest among the provinces on Sumatra Island in 2016. This research is more focused on analyze child poverty in urban areas. This study uses data from the Field Work Practice of Politeknik Statistika STIS Academic Year 2017/2018 held in Bengkulu Province. The analytical method used is nonlinier regression with complementary log-log link function with backward elimination. The results of the analysis show that children who live with household heads are younger, with the education of household heads who are graduated below high school, children who live in households that are more than four household members, and children who live in households that are not having saving behavior is riskier to experience child poverty.